Advances in Autoimmune Epilepsy Associated with Antibodies, Their Potential Pathogenic Molecular Mechanisms, and Current Recommended Immunotherapies - Fang, Zhiwei; Yang, Yunqi; Chen, Xuan; Zhang, Weiwang; Xie, Yangmei; Chen, Yinghui; Liu, Zhenguo; Yuan, Weien (Frontiers in Immunology, 2017)
In this comprehensive article we present an overview of some most common autoimmune antibodies believed to be potentially pathogenic for autoimmune epilepsies and elaborate their pathogenic mode of action in molecular levels based on the existing knowledge. Findings of the studies of immune-modulatory treatments for epilepsy are also discussed and guidelines for immunotherapy are sorted out. We aim to summarize the emerging understanding of different pathogenic mechanisms of autoantibodies and clinical immunotherapy regimens to open up therapeutic possibilities for future optimum therapy. We conclude that early diagnosis of autoimmune epilepsy is of great significance, as early immune treatments have useful disease-modifying effects on some epilepsies and can facilitate the recovery.